Sugarcane as a Forage Plant: Structural and Chemical Traits that Affect Fiber Quality - Rodrigues Marques, Joao Paulo [UNESP]; Aferri, Gabriela; Montanha, Gabriel Sgabieiro; Perassolo Guedes, Fernanda Trilstz; Soares, Marli Misaki; Muniz, Larissa Fernando; Tomazello Filho, Mario; Xavier, Mauro Alexandre; Pereira de Carvalho, Hudson Wallace (North Carolina State Univ Dept Wood & Paper Sci, 2021)
Sugarcane is widely used as feed for cattle, buffalo, goats, and sheep, primarily during drought periods. Some sugarcane cultivars contain low digestibility fibers, which compromises animal performance. Thus, the present study reports on anatomical, chemical, and elemental analysis along stem internodes of two sugarcane cultivars to better understand the structuredigestibility relationship of industrial cultivar cv. IACSP95-5000 compared to a forage cultivar (cv. IAC86-2480). X-ray microdensitometry assays revealed that the peripheral tissues of IACSP95-5000 were denser than IAC86-2480. In the first internode, cv. IACSP95-5000 has more vascular bundles and occupy a larger area. In addition, it had more fibers surrounding the vascular bundles compared to cv. IAC86-2480. However, fibers are prominent at the fifth internode in both cultivars but are more evident in cv. IACSP95-5000. The microprobe X-ray fluorescence spectroscopy analysis showed that silicon and calcium elemental distribution were similar for both cultivars. The structural features of the forage sugarcane presented herein are able to explain the digestibility differences between cultivars.
Keywords: Fibers; Plant anatomy; Microdensity; Microscopy; Saccharum spp.; Structural marker; X-ray; XRF